Students’ Procedural Fluency in Fraction Addition through Built-in Definition Fraction Media - Jelita Herdia Siregar; Darmawijoyo; Septy Sari Yukans; Rahma Siska Utari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
This study aims to describe elementary students’ procedural fluency in solving fraction addition problems using the built-in definition fraction media. Fraction operations are often challenging for students, particularly when determining common denominators and applying calculation procedures accurately. These difficulties are commonly associated with weak procedural understanding and limited opportunities to use concrete learning media. This descriptive study involved 30 fourth-grade students from SDN 204 Palembang who had previously learned basic fraction concepts. Data were collected through a written test consisting of three levels of procedural fluency tasks and supported by interviews to explore students’ reasoning processes. The results show that 47% of students were able to solve fraction addition problems with denominators (Level 1), 33% managed tasks involving adjustment of one denominator (Level 2), and only 13% successfully solved problems requiring the determination of the least common multiple of denominators (Level 3). These findings indicate that students’ procedural fluency development is not linear but constrained at transition points from concrete visual manipulation to abstract procedural reasoning. While the built-in definition fraction media effectively supported early procedural stages by strengthening visual–procedural connections, it was less effective in facilitating higher-level abstraction required for complex fraction operations. The study contributes to procedural fluency literature by identifying specific procedural transition points where students begin to experience difficulties.